Madagascar [videorecording (DVD)]. - Stiller, Ben, 1965-; Rock, Chris; Smith, Jada Pinkett, 1971-; Schwimmer, David, 1966-; Cedric, the Entertainer, 1965- (Dream Work Pictures, 2006)
The friendship between a New York City lion and zebra is tested when fate brings them out to the unforgiving wilderness in this computer-animated DreamWorks feature.